Pathological social withdrawal in autism spectrum disorder: A case control study of hikikomori in Japan - Yamada, Mari; Kato, Takahiro A.; Katsuki, Ryoko Inoue; Yokoi, Hideki; Igarashi, Miki; Komine, Yoko; Kamata, Yukinori; Kato, Nobumasa; Iwanami, Akira; Ohta, Haruhisa (Frontiers in Psychiatry, 2023)
Introduction Hikikomori, a form of pathological social withdrawal, has been suggested to have comorbidity with autism spectrum disorder (ASD). This study aimed to clarify how characteristics of ASD are associated with hikikomori. Methods Thirty-nine adult male patients with a diagnosis of ASD attending our outpatient clinic for neurodevelopmental disabilities were subjected to a structured interview regarding social withdrawal, various self-administered questionnaires, and blood tests. Through structured interviews, the subjects were divided into two groups: (Group 1) ASD with hikikomori condition and (Group 2) ASD without hikikomori condition. Sixteen subjects qualified as hikikomori and 23 subjects qualified as subjects without hikikomori. Age, sex, autism spectrum quotient (AQ), Autism Diagnostic Observation Schedule (ADOS), and FIQ were matched. Results Compared to non-hikikomori controls, hikikomori cases were likely to have stronger sensory symptoms, lower uric acid (UA) (p = 0.038), and higher rates of atopic dermatitis (p = 0.01). Cases showed more severe depressive and social anxiety symptoms based on self-rated scales: Patient Heath Questionnaire 9 (PHQ-9) (p < 0.001) and Liebowitz Social Anxiety Scale Japanese Version (LSAS-J) (p = 0.04). Tarumi's Modern-Type Depression Trait Scale (TACS-22), which measure traits of Modern-Type Depression (MTD), were significantly higher in cases (p = 0.003). Conclusion The present study has suggested that ASD patients with hikikomori were more likely to have higher sensory abnormalities, comorbid atopic dermatitis, lower UA, stronger depressive, and anxiety tendency. Evaluating and approaching these aspects are important for appropriate interventions in ASD with hikikomori. Further investigations should be conducted to validate our pilot findings.